Groundwater vulnerability assessment in Randublatung groundwater basin using SINTACS-LU model. Issue 1 (1st September 2022) - Hartono, A; Hendrayana, H; Akmaluddin,
Abstract: Randublatung groundwater basin is one of the crucial areas in Central Java that involves agricultural activities, which rely on groundwater sources. Agricultural activities have impacted the declining groundwater excellent of the Randublatung groundwater basin. The groundwater exploration was executed from an unconfined shallow aquifer that is in particular composed of alluvial deposits. Therefore, vulnerability evaluation to delineate regions most vulnerable to contamination from anthropogenic resources has come to be essential for sensible useful resource management and land use planning. This study estimates groundwater vulnerability by applying the SINTACS-LU model, which uses eight parameters to assess groundwater vulnerability and the geographical information system (GIS) in the Randublatung groundwater basin. The final subject level of SINTACS-LU (intrinsic vulnerability index) was created by multiplying the sum of each evaluation parameter by its specific weight. The resultant SINTACS-LU vulnerability map of the study area indicates that the areas most likely to be contaminated are between Kradenan and Keduntuban districts. Elsewhere, Rather high to high SINTACS-LU index values were observed, indicating areas of high vulnerability potential.